2023
DOI: 10.1063/5.0134667
|View full text |Cite
|
Sign up to set email alerts
|

The network structure of the corneal endothelium

Abstract: A generic network model is applied to study the structure of the mammalian corneal endothelium. The model has <p>been shown to reproduce the network properties of a wide range of systems, from low-dimensional inorganic glasses</p> <p>to colloidal nanoparticles deposited on a surface. Available extensive experimental microscopy results are analysed</p> <p>and combined to highlight the behaviour of two key metrics, the fraction of hexagonal rings ($p_6$) and the</p> <p>c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Lemaître's law is the virial equation of state for two-dimensional cellular networks, which relates two measures of disorder (i.e., thermodynamic variables), namely, the fraction of hexagons to the width of the polygon distribution [11,19,20,[39][40][41]. Although at first proposed for two-dimensional foams, it has been shown that a wide range of planar cellular networks in nature obey Lemaître's law, ranging from biology such as avian cones [30], epithelial cells [42], and mammalian corneal endothelium [43], to physics such as amorphous graphene [41], the Ising model [44], Bénard-Marangoni convection [45], silicon nanofoams [46], and silica bilayers [47]. It can be obtained by maximizing the entropy, H = − ∑ n≥3 p n ln p n , where p n is the probability, or the frequency of the appearance, of an n-sided polygon, while considering the following information:…”
Section: Lemaître's Lawmentioning
confidence: 99%
“…Lemaître's law is the virial equation of state for two-dimensional cellular networks, which relates two measures of disorder (i.e., thermodynamic variables), namely, the fraction of hexagons to the width of the polygon distribution [11,19,20,[39][40][41]. Although at first proposed for two-dimensional foams, it has been shown that a wide range of planar cellular networks in nature obey Lemaître's law, ranging from biology such as avian cones [30], epithelial cells [42], and mammalian corneal endothelium [43], to physics such as amorphous graphene [41], the Ising model [44], Bénard-Marangoni convection [45], silicon nanofoams [46], and silica bilayers [47]. It can be obtained by maximizing the entropy, H = − ∑ n≥3 p n ln p n , where p n is the probability, or the frequency of the appearance, of an n-sided polygon, while considering the following information:…”
Section: Lemaître's Lawmentioning
confidence: 99%
“…Lemaître’s law is the virial equation of state for two-dimensional cellular networks, which relates two measures of disorder (i.e., thermodynamic variables), namely, the fraction of hexagons to the width of the polygon distribution [11,18,19,3133]. Although at first proposed for two-dimensional foams, it has been shown that a wide range of planar cellular networks in nature obeys Lemaître’s law, ranging from biology such as avian cones [23], epithelial cells [34], and mammalian corneal endothelium [35], to physics such as amorphous graphene [33], the Ising model [36], Bénard–Marangoni convection [37], silicon nanofoams [38], and silica bilayers [39]. It can be obtained by maximizing the entropy, H = − ∑ n ≥3 p n ln p n , where p n is the probability, or the frequency of appearance, of an n -sided polygon, while considering the following information: The first relation is the normalization condition, and the second one is a consequence of Euler’s relation concerning the topology of the structure, which assumes only three lines meet at a vertex.…”
Section: Lemaître’s Lawmentioning
confidence: 99%